PEMIDANAAN TERHADAP PELAKU MANIPULASI INFORMASI DOKUMEN ELEKTRONIK SECARA BERLANJUT (Studi Putusan Nomor 242/Pid.Sus/2020/PN Tbt) - FARISMAN AMAZIHONO (Jurnal Panah Hukum, 2023)
Along with the increasingly widespread utilization and use of electronic information and transactions, it is like a double-edged sword, because in addition to contributing to increasing human welfare, progress and civilization, it is also an effective means of acting against the law. As in the conventional world which is full of legal problems, cybersurfers are also increasingly seeing legal problems in the world of cyberspace (cyberspace). For this reason, humans want to know about cyber-related crime through research, while the research used is normative legal research with statutory approach methods, case approach methods and analytical approach methods. In this study, data collection was carried out using secondary data obtained through library materials consisting of primary legal materials, secondary and tertiary legal materials. The data analysis used was qualitative data analysis and conclusions were drawn using the deductive method. Based on the results of the research findings and discussion, it can be concluded that the sentencing of the perpetrators of manipulating electronic document information continues through the study of decision number 242/Pid.Sus/2020/PN TBT, by the judge in his decision sentenced the defendant to imprisonment for 1 (one) year year and 2 (two) months. According to the author of the sentence given to the defendant by the judge there is no deterrent effect which can make the offender feel guilty and it is possible that in the future he will commit the same act because he feels that the sentence given is still relatively light, bearing in mind that one of the goals of punishment is to deter people from people who have committed crimes By obeying and enforcing the law properly, it can create order and regularity in society